Distance Learning Policy During Pandemic Covid-19 - Maya Puspita Dewi; Muh Barid Nizarudin Wajdi (STAI Miftahul Ula Nganjuk, 2021)
This study aims to analyze the learning process online, supporting factors and factors inhibiting teachers in carrying out online learning during the covid-19 pandemic. This research was conducted in several elementary schools in Nganjuk district which is calculated from September to January 2021. This study uses a type of descriptive qualitative method research. The subjects used in this study were primary school teachers and some education-related policymakers. Data collection techniques used in this study in the form of open questionnaires, semi-structured interviews, documentation and field records. The result of this study is that the covid-19 pandemic has a huge impact on the learning process, learning that is usually carried out directly is now diverted into online learning. Students feel bored and bored during the learning. Online learning for primary school-age children is less effective. There are several factors supporting teachers in the online learning process, namely the availability of mobile phones, quotas and a stable internet network. In addition to the supporting factors in online learning there are also several factors inhibiting teachers in online learning. The inhibitory factors include that not all students have mobile phones and many parents are busy working.it is necessary to government from various parties, both from the government as the regulatory holder and the community as policy users. so it is expected that both can synergize and maximize the academic potential of students.